2013
DOI: 10.1016/j.ijcard.2012.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility limits of transradial primary percutaneous coronary intervention in acute myocardial infarction in the real life (TRAP-AMI)

Abstract: In STEMI patients without cardiogenic shock and without a priori indication for TFI, PCI can be performed via the radial artery in more than 90% of cases with high procedural success rate. Operator's judgement of eligibility for TRI based on radial pulse quality is predictive of successful TRI in 95% of cases. TR failure is significantly more common in the elderly and in patients with low body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Mamas et al [16] recently reported data on the nationwide practice of PCI in the UK, showing highly variable rates of radial approach use between centres, with an overall rate of use of only 26%. The feasibility of PCI by radial access is clearly lower than the 90% recently described in a 'real-life' population of uncomplicated ST-elevation MI [18]. Indeed, CS is a strong independent predictor of transradial approach PCI failure [19].…”
Section: Discussionmentioning
confidence: 87%
“…Mamas et al [16] recently reported data on the nationwide practice of PCI in the UK, showing highly variable rates of radial approach use between centres, with an overall rate of use of only 26%. The feasibility of PCI by radial access is clearly lower than the 90% recently described in a 'real-life' population of uncomplicated ST-elevation MI [18]. Indeed, CS is a strong independent predictor of transradial approach PCI failure [19].…”
Section: Discussionmentioning
confidence: 87%
“…Crossover from TRA to TFA in primary PCI for STEMI in recent studies has been reported to range from 3.7% to 9.6% 13 14 28 29. However, current real world data on predictors of TRA-PCI failure in the STEMI population are very scarce, and limited to selected cohorts 19 20…”
Section: Discussionmentioning
confidence: 99%
“…Some retrospective studies reporting on TRA failure rate and predictors were limited by heterogeneity of patients, in addition to overall TRA volume,18 while others were selective, and excluded patients presenting with cardiogenic shock complicating STEMI 19 20 29. Vink et al 19 recently examined the feasibility of routine TRA in primary PCI (excluding cardiogenic shock) in a single centre where TRA was the default for >10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous coronary intervention (PCI) performed via the transradial approach is associated with a lower risk of major vascular complications and a lower risk of major bleeding at the access site than PCI via the transfemoral approach in patients with acute coronary syndrome [2,3] and in patients with acute ST-segment elevation who require primary coronary intervention and aggressive antithrombotic treatment [4,5]. Nevertheless, bleeding at the radial access site can lead to forearm hematoma and rarely, to compartment syndrome [6].…”
mentioning
confidence: 99%
“…The possible reasons for delayed onset of the syndrome in our patient include radial artery atherosclerosis with inadequate contraction after hemostatic band compression and overdose of unfractionated heparin (640 units/h). Studies have shown that compartment syndrome after transradial coronary intervention is rare (b 0.01%) [7] but tends to be more common in the elderly with low body weight [5]. Activated partial thromboplastin time/activated clotting International Journal of Cardiology 178 (2015) 77-78 time and the condition of the vascular access site should be closely monitored to prevent compartment syndrome.…”
mentioning
confidence: 99%